HUBUNGAN DIPLOMATIK ANTARA KOREA UTARA DAN MALAYSIA PASCA TERBUNUHNYA KIM JONG NAM DITINJAU DARI KONVENSI WINA 1961 - Putu Febrilia Maha Yani; Dewa Gede Sudika Mangku; Ratna Artha Windari (Program Studi Ilmu Hukum, 2018)
This study aims to (1) examine the history and the opening of diplomatic representation under review from the Vienna Convention of 1961 and also (2) to know the legal consequences for the severance of diplomatic relations between North Korea and Malaysia after Kim Jong Nam's assassination. The type of research used is normative, where the author review of the Conventions associated with the case in the problems raised by researcher. This research approach uses approach of legislation, case approach and historical approach. Sources of legal materials used are primary, secondary and non-legal sources of law. Techniques of collecting legal materials by library study with the processing of legal materials undertaken deductively. Based on the discussion of (1) The relationship between Malaysia and North Korea began on 30 June 1973. The two countries opened their embassies in their respective capitals in 2003. (2) In diplomatic relations there are also disconnections which may cause legal consequences. In Article 45 of the Vienna Convention 1961, in the event of diplomatic break-up between the two countries, the receiving country shall protect and respect its diplomatic representative's premises and the protection of property including its archives in the event of an armed conflict, if the diplomatic representation has been closed and the diplomatic representative building has been belongs to the sending country, the sending country may entrust control of its diplomatic representative's premises to a third country